Análise da influência de fatores macroeconômicos no desempenho de empresas da indústria química - Furtado, Natália de Souza (Universidade Federal de São Carlos, 2024)
This study proposed to analyze and understand how the basic interest rate of the Brazilian economy and the exchange rate of the dollar against the real affect the financial performance of key companies in different segments of the chemical industry: Ambev, currently the company with the largest market share in the brewing sector in Brazil; and Vale S/A, one of the largest mining companies globally. As a methodology, data on revenue, profit, manufacturing costs, and loan and financing amounts of the two selected companies were collected over the period from 2013 to 2023. Simultaneously, data on the Selic interest rate, exchange rate, IPCA, and the historical prices of the main raw materials for the companies' industrial processes were gathered. The collected data were compared through scatter plots, and the results were analyzed and supported by market data and macroeconomic concepts. It was concluded that, during the analyzed period, the appreciation of the dollar against the real was beneficial only for Vale in terms of profit margin, given the strong dependence on exports of the mining company, which is not the case for the brewery. Additionally, it was found that all the main raw materials of both companies showed strong correlations with the exchange rate. It was not possible to determine the influence of the Selic rate on both companies, given the low correlation coefficient obtained from the comparisons.
Analysis of the influence of macroeconomic factors on performance of companies in the chemical industry
Keywords: Macroeconomia; Indústria; Indicadores; Cevada; Minério de ferro; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA